Gottron's carcinoid papillomatosis of the skin (сlinical case) - O.M. Biesiedin; V.M. Shkuropat; K.V. Tsygankov; P.O. Hrytsenko; S.V. Biletska (Medičnì Perspektivi)
Gottron's carcinoid papillomatosis of the skin is a rare and little-studied disease. The number of available scientific publications does not exceed several dozens, in Ukraine, in the last ten years, 2 works devoted to this pathology have been published. However, in parallel with the increase in diagnostic capabilities in a multidisciplinary hospital, there are periodically cases of establishing a diagnosis: Gottron's carcinoid papillomatosis of the skin. The lack of a clear understanding of the diagnostic and treatment algorithm creates additional difficulties in the treatment of Gottron's carcinoid papillomatosis of the skin. The course and features of this disease, namely: the presence of various concomitant pathologies, duration and unsatisfactory results of treatment, low patient compliance, etc., make its study relevant. This prompts a more detailed study and analysis of cases of successful treatment. The purpose of our work was to analyze a clinical case of treatment of Gottron's carcinoid papillomatosis of the skin in a multidisciplinary hospital using a multidisciplinary team approach, as well as to summarize the data related to the incidence, features of the clinical course and treatment of this disease given in scientific publications. A clinical case of successful treatment of a patient with Gottron's carcinoid papillomatosis of the skin is presented, a model of the interaction of a vascular surgeon at the stage of restoring the patency of the main arteries and preservation of the limb, a surgeon of the purulent-septicsurgery department at the stage of local and systemic treatment, a pathologist at the diagnostic and post operative stage, and a dermatologist for improvement of topical exposure and ambulatory monitoring is shown. Therefore, the analysis of this clinical case convincingly testifies to the successful capabilities of a multidisciplinary hospital in the treatment of Gottron's carcinoid papillomatosis of the skin, which can be taken into account when determining the treatment tactics of this disease. Coverage of this and similar cases in scientific publications of this rare disease will improve clinician awareness and treatment outcomes.